Investigação numérica e experimental de dispositivos piezelétricos combinando geração de energia e atenuação de vibrações - Tsuruta, Karina Mayumi (2015)
In the research work carried out under this thesis it is investigated the possibility of combining the passive vibration control and the generation of electricity from the vibratory motion. In this context, the central aim of the thesis is the development, including design, numerical and experimental evaluation devices for simultaneous performance as piezoelectric energy generators (PEH) and dynamic vibration absorbers (DVA), called PEH/DVA. In order to consider practical situations in which a device of this type must be connected to a vibrating structure called primary structure (PS), the study has emphasized the characterization of dynamic interactions between EP and PEG/DVA, since these interactions determine the efficiency of PEH/DVA in terms of vibration control and power generation. A general structural formulation was developed containing piezoelectric transducers connected to resistors in which both the PEH/DVA and PS were considered continuous vibratory subsystems discretized with various degrees of freedom. In the numerical simulations performed using computer codes implemented in MATLAB® environment, these two subsystems were modeled as beams of Euler-Bernoulli. The simulations were aimed, first, to the characterization of the dynamic interactions between the two subsystems, and subsequently, the optimization of PEH/DVA with towards to maximize its functionality. For the experimental study a new configuration of PEH/DVA called cruciform (PEH/DVA-C) prototype was designed, constructed and experimentally tested. It was built using four aluminum blades in the balance sheet, arranged in a cross, and the surface of each blade a ceramic piezoelectric transducer has been glued. The four transducers were connected electrically in series, such a way that when the blades undergo deflection, the electrical voltages produced by the transducers are summed. Concentrated masses at the free ends of the blades were added to increase the level of vibration and to facilitate the adjustment of the natural frequencies of the PEH/DVA-C according to the excitation frequency. The PEH/DVA-C was connected to a trussed structure measuring about six meters long. The tests allowed to observe the electromechanical behavior of the device due to some operational variables, evidencing its ability to load a lithium battery when the trussed structure was excited by imbalance forces.